In Vitro Effect of Anodization of Titanium Abutments on Color Parameters and Color Difference of Lithium Disilicate All‐Ceramic Crowns - Sotude Khorshidi; Arash Zarbakhsh; Shirin Lawaf; Shaghayegh Golalipour; Maryam Sayyari; Alireza Mahmoudi Nahavandi (Wiley, 2024)
ABSTRACT Objective This study assessed the effect of the anodization of titanium abutments on the color parameters and color difference of lithium disilicate (LDS) all‐ceramic crowns. Materials and Methods In this study, 19 straight abutments were divided into two groups: anodized (n = 9) and non‐anodized control (n = 9), with one hybrid zirconia abutment as a reference. Anodization was achieved by applying 63 V energy using seven 9 V flat batteries in series, with an electrolyte solution comprising 1 g trisodium phosphate in 250 mL distilled water for 5 s, resulting in a gold‐yellow color. Abutments were then scanned, and full‐contour monolithic IPS e.max maxillary central incisor crowns were fabricated with 2 mm thickness and glazed. Reflectance was measured using a spectroradiometer, and color coordinates (L*, a*, b*, h*, and C*) were calculated using CS‐10W software. Color differences of the crowns in both groups were quantified using the CIEDE2000 (ΔE00) color difference formula and analyzed by t‐test (α = 0.05) compared to the standard sample. Results The L*, a*, b*, and c* parameters in anodized abutments were significantly higher than those in non‐anodized abutments, while the h* parameter in anodized abutments was significantly lower than that in non‐anodized abutments (p < 0.001 for all). There was a significant difference in ΔE00 of the two groups (p = 0.043). Conclusion Anodization of titanium abutments improved the color parameters of LDS all‐ceramic crowns and significantly decreased their ΔE compared with non‐anodized abutments.